UZBEKISTAN'S NEW CURRENCY POLICY AND INTEGRATION INTO INTERNATIONAL MARKETS - Tolibov Abdulloh (The Conference Hub, 2025)
This scientific work is devoted to the study of the new currency policy of Uzbekistan and its integration into international markets. The main goal of the work is to ensure the stability of the national currency, control inflation, and develop an effective integration strategy with the international economic system.
Keywords: Uzbekistan, currency policy, international markets, integration, inflation, digital currency, cryptocurrency.